Can patients suffering an ST elevation myocardial infarction enjoy a similar life expectancy to that of the general population?. (26th April 2021) - Almendarez Lacayo, M; Pascual, I; Avanzas, P; Adeba, A; Vigil-Escalera, M; Arboine, L; Alvarez, R; Hernandez-Vaquero, D; Moris De La Tassa, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction and objectives: There has been a continuous process of improvement after (ST-segment elevation myocardial infarction) STEMI. Our aim was to know whether patients < and ≥ 65 years suffering a STEMI can recover a life expectancy similar to that of the general population of the same age, sex and geographical region. Methods: We included all patients who suffered a STEMI from January 2014 until January 2020 and compared them to a reference population provided by the National statistics Institute from Spain. For those patients surviving the acute event as well as the first 30 days, we calculated their observed survival, expected survival and the excess of mortality calculated with the Ederer II method. If the expected survival was inside the 95% confidence interval(CI) of the observed survival there was not a significant excess of mortality. We repeated all analyses for survivors stratifying by 65 years. Results: We included 1722 patients, 899 patients were <65 years. For patients < 65 years who survived a STEMI, observed survival at 3 and 5 years of follow-up was 97.68%(95%CI, 96.05%-98.64%) and 94.14%(95%CI, 90.89%-96.25%), respectively. Expected survival for 3 and 5 years was 98.12% and 96.61%. For patients ≥ 65 years who survived the STEMI, observed survival at 3 and 5 years was 85.52%(95%CI, 82.23%-88.24%) and 75.43%(95%CI, 70.26%-79.83%), respectively. Expected survival for 3 and 5 years was 86.48% and 76.56%. Conclusions: For survivors of the acute event, life expectancy is similar to that of the general population of the same age, sex and geographical region.